Business Feasibility and Income Level of Seaweed Kappahycus alvarezii Cultivators in Bobanehena Village, Jailolo Subdistrict, West Halmahera Regency - Fatma Muchdar; Muhammad Irfan; Gamal M. Samadan; Sandra Sriwahyuni (Sangia Publishing, 2020)
Seaweed K.alvarezii is a type of seaweed from the red algae (Rhodophyta) group that produces carrageenan.Carrageenan is very important as a thickening, gelling and emulsifying agent, and is widely used in various industries such as food, pharmaceuticals, cosmetics, soap, textiles, paints, toothpaste and others. Bobanehena Village, Jailolo Subdistrict, is one of the areas in West Halmahera that has been used by the local community as a seaweed K.alvarezii type of seaweed cultivation area since 2007, but it has not yet provided optimal results.To find out the extent of the impact of this business in providing benefits both financially and the level of income of seaweed cultivators in the area, it is necessary to study in depth through research. The purpose of this study was to determine the feasibility of seaweed K.alvarezii cultivation, and the income level of seaweed K.alvarezii cultivators in Bobanehena village, Jailolo subdistrict,West Halmahera regency.This research was conducted at the location of seaweed cultivation in Bobanehena Village, Jailolo subistrict, West Halmahera Regency.The time of the research was 1 (one) month, starting from November to December, 2019. Data collection was carried out on all selected respondents.The number of cultivators selected as respondents consisted of 7 groups, each of which consisted of 10 people who carried out the seaweed K. alvarezii cultivation business.The number of cultivators was randomly selected (rendom) so that the total number of seaweed cultivators was 70 people. The data collection method was carried out by survey and interview methods. The results showed that the seaweed K.alvarezii cultivation business in Bobanehena village, Jailolo subdistrict was feasible to be cultivated or developed because it had an R/C ratio > 1, with a total income level of Rp./year or Rp. 210,234,200/harvest season or Rp. 30,033,457/ group/ha.